Annual Reports of the City Officers and City Boards of the City of Saint Paul 689 (1888) - (:unkn) unknown (My University, 1888)
No. 6: Prohibited carrying fire arms, throwing stones, or other missiles in any park or within fifty yards thereof.
Keywords: CARRY - CERTAIN PUBLIC PLACES